PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP LABA BERSIH PADA PT TELKOM INDONESIA (PERSERO) TBK PERIODE 2011-2022 - Unjani, Mega; Al Choir, Fikron (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to find X1-Y, The research method used is a quantitative method. The data in this research is secondary data obtained from the financial reports of PT Telkom Indonesia (Persero) Tbk. Data analysis techniques used include descriptive analysis, classical assumption testing, multiple linear regression analysis, hypothesis testing and coefficient of determination. Based on the results of this research, it shows that in partial terms the Current Ratio (CR) obtained Tcount < Ttable, namely 0.653363 < 1.83311 and the significance value is 0.5299> 0.05 which shows that it has no significant effect on Net Profit, Debt to Asset The partial ratio (DAR) shows Tcount<Ttable, namely 2.428334>1.83311 and a significant value, namely 0.0381<0.05, which shows a significant effect on Net Profit. The results of simultaneous testing of the Current Ratio (CR) and Debt to Asset Ratio (DAR) obtained Fcount<Ftable, namely 4.181080 < 4.26 and a significance value of 0.051985> 0.05, this shows that there is no simultaneous influence between the Current Ratio and Debt to Asset Ratio to Net Profit.